About Diatom’s Study of Kozache-Lagers’ka Arena in the “Oleshkivs’ki Piski” National Nature Park (Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Data on diatoms species composition of National Nature Park “Oleshkivski Piski” are given for the first time. The checklist consists of 46 species with 3 of them new to Ukraine, such as Navicula vilaplanii (Lange–Bert. et Sabater) Lange–Bert. et Sabater, Pinnularia sinistra Krammer and Stauroneis obtusa Lagerstedt.
Keywords: Bacillariophyta, diatoms, epiphytes, shallow lakes.